Method for improving stability of metal halide perovskite, material and application
By doping methylenediamine cations at the A-position of perovskite lattice, the problems of ion migration and halogen segregation in perovskite materials are solved, and the stability and photoelectric properties of the materials and devices are significantly improved.
Patent Information
- Application Number
- CN202510068855.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The stability of metal halide perovskite materials and their devices is one of the main obstacles to their commercialization process, especially the halogen segregation problems of ion migration and wide-bandgap perovskites are difficult to effectively suppress.
The A-position doped cationic species with charge number ≥2 are used to dope at the A-position of the halide perovskite lattice. The salt of methylenediamine cation (MDA2+) is used to achieve the preparation of perovskite precursor solutions and thin film preparation methods. Doping of heterovalent cations on the A-position of perovskite lattice.
It significantly inhibits the ion migration in perovskite materials and the halogen segregation problems of wide bandgap perovskites, improves the stability and photoelectric performance of materials and devices, and improves the photoelectric conversion efficiency.
Smart Images

Figure CN119462732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor optoelectronic devices, and in particular to a method, material and application for improving the stability of metal halide perovskite. Background Art
[0002] Metal halide perovskite solar cells are a new type of photovoltaic technology that has developed extremely rapidly in the past decade and has great industrial prospects. They have the advantages of simple structure, high photoelectric conversion efficiency, and easy preparation. At present, the conversion efficiency of single-cell perovskite solar cells has exceeded 26%, approaching the most advanced silicon heterojunction solar cells (26.8%). In addition, tandem solar cells based on halide perovskites (including silicon-perovskite tandems, copper indium gallium selenide-perovskite tandems, perovskite-perovskite tandems, and organic-perovskite tandems) are photovoltaic technologies with higher photoelectric conversion efficiency than single-cell solar cells and are the mainstream development direction of the next generation of more efficient photovoltaic technologies. However, the stability problem of halide perovskite materials and their devices is one of the main obstacles to their commercialization. Metal halide perovskite is a soft ionic compound semiconductor material, and its general chemical formula can be expressed as ABX3, where the A position is an organic or inorganic monovalent cation, such as CH3NH3 + (MA + ), CH(NH2)2 + (FA + ), and cesium ions (Cs + ); the B position is a divalent lead ion (Pb 2+ ), tin ions (Sn 2+ ); X is a halogen anion, with iodide ion (I - ) and bromide ion (Br - ). The weak chemical interactions between its components and the special crystal structure make its ion migration activation energy low, its thermal stability poor, and it is easy to react with water, oxygen, etc., which affects the life of the material and the device. In addition, the preparation of perovskite-based tandem solar cells requires perovskite materials with wider band gaps, which can be achieved by increasing the proportion of Br components in the material, but this is accompanied by the problem of halogen segregation (or phase separation), especially under the action of light and electric field. How to effectively inhibit ion migration in perovskite materials and further inhibit the halogen segregation problem of wide-bandgap perovskites has become an important topic of common concern in academia and industry. The existing technologies for specifically inhibiting ion migration and phase segregation problems in halide perovskites can be mainly summarized into the following categories: (1) using large-sized organic amine salts to form two-dimensional perovskites at the perovskite grain boundaries and / or surfaces; (2) increasing Cs at the A position; and (3) increasing the number of Cs at the A position. + Component content; (3) Add Cl at position X -The above methods have different degrees of improvement on the ion migration and photoinduced phase separation problems. However, the technical solutions of using multivalent cation doping at the A site to inhibit ion migration and applying it in wide bandgap perovskites to improve the halogen segregation problem have not yet been developed. Summary of the invention
[0003] The purpose of the present invention is to provide a method, material and application for improving the stability of metal halide perovskite. The method of the present invention has a significant inhibitory effect on ion migration and wide-bandgap perovskite phase segregation. In addition, the present invention also provides the application of the perovskite material or film obtained by this method in optoelectronic devices.
[0004] The purpose of the present invention can be achieved by the following technical solutions: A method for improving the stability of metal halide perovskite comprises: doping a cationic species with a charge number ≥ 2 at the A position of the halide perovskite lattice.
[0005] The halide perovskite is an ABX3 type halide perovskite, and the A-position component is CH3NH3 + (MA + ),CH(NH2)2 + (FA + ), cesium ion (Cs + ) in one or more combinations; the B component is lead ion (Pb 2+ ), tin ions (Sn 2+ ) or a combination of two thereof; X is an iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - )
[0006] Furthermore, the cationic species with a charge number ≥ 2 include methylenediamine cation (MDA 2+ ) of salt.
[0007] Furthermore, the methylenediamine cation (MDA 2+ ) includes one or more of methylenediamine dihydrochloride (MDACl2), methylenediamine dibromide (MDABr2), methylenediamine diiodide (MDAI2), methylenediamine dithiocyanate (MDA(SCN)2), methylenediamine diformate (MDA(HCOO)2), methylenediamine diacetate (MDA(CH3COO)2), methylenediamine oxalate (MDA(C2O4)), methylenediamine dibenzoate, and methylenediamine di-p-toluate.
[0008] Furthermore, the method for implementing the A-site lattice doping includes containing a certain concentration of methylenediamine cation (MDA 2+ ) salt-based perovskite precursor solution preparation and film preparation.
[0009] The certain concentration of the perovskite precursor solution is in the range of 0.1-5 mol% (relative to the molar concentration of the B-site cation), and the preferred concentration is 0.2-3 mol%.
[0010] The preparation of the perovskite precursor solution includes a one-step precursor solution and a two-step precursor solution.
[0011] Furthermore, the one-step precursor solution preparation is to prepare the perovskite precursor material and the methylenediamine cation (MDA 2+ ) salts are weighed in proportion, and then a solvent is added to dissolve. The solvent is one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), γ-butyrolactone (GBL), N-methylpyrrolidone (NMP), and 2-methoxyethanol (2-ME). Preferably, DMF / DMSO is used as the solvent in a volume ratio of 4:1. Stir or shake until fully dissolved. The concentration range of the perovskite solution is 1.0~2.0mol / L, and the preferred concentration is 1.2~1.7mol / L.
[0012] The two-step method for preparing the precursor solution is to prepare the lead-containing, Cs-containing precursor and the organic amine salt precursor separately to form two precursor solutions, wherein the methylenediamine cation (MDA 2+ ) salt can be mixed in any of the two solutions. Wherein, the solvent used is at least one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), γ-butyrolactone (GBL), N-methylpyrrolidone (NMP), 2-methoxyethanol (2-ME), isopropanol (IPA), and water (H2O). Preferably, DMF / DMSO is used as the solvent for lead-containing and Cs-containing precursors, with a volume ratio of 9:1~9.5:0.5; the solution concentration range is 1.0~2.0mol / L, and the preferred concentration is 1.2~1.7mol / L. IPA is used as the solvent for the organic amine salt, and a trace amount of H2O is added, with a volume ratio of 0.5%~3%; the solution concentration range is 0.3~1.2mol / L, and the preferred concentration is 0.45~0.7mol / L.
[0013] Furthermore, the method for preparing the perovskite film includes one or more of a one-step spin coating method, a two-step spin coating method, a doctor blade method, a slit coating method, a vapor deposition combined with a solution deposition method, an inkjet printing method, and a screen printing method. And it is prepared by a subsequent thermal annealing process. The annealing temperature is 90-200°C, preferably 100-120°C; the annealing time is 5-60 minutes, preferably 15-30 minutes; the thickness of the obtained perovskite film material is 400-1500 nanometers, preferably 500-1000 nanometers.
[0014] A method for improving the stability of metal halide perovskite is obtained by using the above method to achieve doping of a cationic species with a charge number ≥ 2 at the A position of the halide perovskite lattice. In particular, the cationic species with a charge number ≥ 2 is a methylenediamine cation (CH2(NH3) 2+ ,MDA 2+ ).
[0015] The invention also discloses the application of the halide perovskite material or film prepared by the method in perovskite solar cells and stacked solar cells.
[0016] Furthermore, the perovskite solar cell comprises a cell substrate, a hole transport layer (or an electron transport layer), a perovskite active layer, an electron transport layer (or a hole transport layer), and a top electrode or a back electrode stacked in sequence.
[0017] Furthermore, the battery substrate includes a transparent conductive flexible substrate, a transparent conductive glass substrate, as well as a silicon-based solar cell, a CIGS solar cell, a narrow-bandgap perovskite solar cell, an organic solar cell, and the like.
[0018] Furthermore, the hole transport layer is one or more of a conjugated organic small molecule containing a phosphoric acid group, nickel oxide, CuSCN, CuI, CuS, molybdenum oxide, copper phthalocyanine, copper-nickel composite oxide, a polymer of 3-hexylthiophene (P3HT), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS).
[0019] Furthermore, the perovskite active layer is a halide perovskite film doped with methylenediamine cations.
[0020] Furthermore, the electron transport layer includes one or more of C60, PCBM, SnO2, TiO2, ZnO, SrTiO3, and BaSnO3.
[0021] Furthermore, the back electrode or top electrode includes one or more of gold, silver, copper, carbon, fluorine-doped tin oxide (FTO), tin-doped indium oxide (ITO), aluminum-doped zinc oxide (AZO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), cerium oxide-doped indium oxide (ICO), and gallium and aluminum co-doped zinc oxide (GAZO).
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The divalent organic cation used to improve the stability of the perovskite in the present invention is a divalent organic cation doped at the A position of the perovskite lattice with a certain amount of methylenediamine cation (MDA 2+ ). MDA 2+ The appropriate ion size makes it a divalent organic cation that can enter the A site of the perovskite lattice. Being able to occupy the A site means that MDA 2+ The cation has better stability and bulk compatibility than other interstitially doped multivalent cations, and has a wider doping concentration window while maintaining beneficial effects. It can form stronger electrostatic interactions with the easily migrating iodine and bromine anions in perovskite, thereby significantly improving the migration activation energy of iodine and bromide ions, inhibiting perovskite phase separation, and improving the stability of films and devices.
[0023] (2) In addition to significantly improving the stability of perovskite materials and devices, the method disclosed in the present invention can also reduce the defect state density of perovskite films, improve the photoelectric performance of devices, and prepare perovskite single-cell and perovskite-based tandem solar cells with higher photoelectric conversion efficiency.
[0024] (3) The present invention achieves heterovalent cation doping of the A position of the perovskite lattice by simply adding the dopant to the perovskite precursor solution through solution film formation and subsequent annealing. The process is simple, the cost is low, and the effect is significant. It is suitable for widespread adoption of perovskite photovoltaic technology in future industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0026] Figure 1 Schematic diagram of the structure of the perovskite solar cell prepared in Example 1 and Example 2; Figure 2 The solar cells prepared in Example 1 and Comparative Example 1 are JV Curve comparison; Figure 3The curve obtained by first-order derivation of the EQE curve of the wide bandgap perovskite solar cell prepared in Example 2; Figure 4 The wide bandgap perovskite solar cells prepared in Example 2, Example 3 and Comparative Example 2 are JV Curve comparison; Figure 5 A schematic diagram of the structure of a copper indium gallium selenide-perovskite tandem solar cell prepared in Example 4; Figure 6 A schematic diagram of the structure of a perovskite-perovskite tandem solar cell prepared in Example 5; Figure 7 This is a schematic diagram of the structure of the silicon-perovskite tandem solar cell prepared in Example 6. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. The following embodiments are provided to better further understand the present invention, are not limited to the best implementation mode, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts falls within the protection scope of the present invention.
[0028] 1. Preparation of perovskite solar cells
[0029] Example 1: This example provides a method for preparing a perovskite solar cell, wherein the band gap of the perovskite film material is about 1.53 eV, belonging to a narrow band gap metal halide perovskite cell, and the cell structure is as follows Figure 1 As shown, it includes five parts: indium tin oxide (ITO) glass substrate as the battery substrate, hole transport layer, perovskite active layer, electron transport layer and metal electrode. The specific preparation steps are as follows: S1: Setting the battery substrate; S1-1: Clean the ITO glass substrate, use detergent, deionized water, ethanol, acetone, and ethanol for ultrasonic cleaning for 15 minutes each. After cleaning, use a nitrogen gas flow to blow dry the substrate, and then treat it with ultraviolet ozone for 15 to 30 minutes, and in this embodiment, the treatment is 20 minutes.
[0030] S2: Preparation of hole transport layer: S2-1: Preparation of NiO x Nanocrystal aqueous solution: nickel oxide (NiO x) Add nanocrystalline powder to ultrapure water, the concentration in this embodiment is 10 mg / mL. Oscillate and sonicate for 5 min each. Filter through a 0.45 μm pore size polytetrafluoroethylene filter membrane and set aside; S2-2: preparing an organic solution of a conjugated organic small molecule containing a phosphate group: specifically, using [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz for short) to prepare an anhydrous ethanol solution of Me-4PACz with a concentration of 0.5-1.0 mg / mL, 1.0 mg / mL in this embodiment, shaking and ultrasonicating for 5-15 min each, 10 min in this embodiment, and filtering with a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm for later use; S2-3: Take the prepared NiO x The aqueous solution of nanocrystals was spin-coated on an ITO glass substrate at 3000 rpm and then annealed at 150 °C for 15 min in clean air and then immediately transferred to a glove box; S2-4: In a nitrogen glove box, a solution of Me-4PACz in anhydrous ethanol was spin-coated on the prepared NiO at a speed of 3000 rpm. x The resulting film was placed on a substrate with a layer and then annealed at 110°C in a glove box for 10 min.
[0031] S3: Preparation of perovskite active layer: S3-1: Preparation of perovskite precursor solution: MDA in this embodiment 2+ The doping concentration of the cation is 0.75 mol%. Specifically, a perovskite precursor solution containing lead iodide (PbI2), lead bromide (PbBr2), cesium iodide (CsI), methylamine iodide (FAI), methylamine bromide (MABr), methylamine chloride (MACl), methylenediamine dihydrochloride (MDACl2), and rubidium iodide (RbI) with DMF and DMSO as a mixed solvent is prepared, and the feed ratio of each substance is 682 mg: 12.03 mg: 20.8 mg: 256 mg: 3.41 mg: 11.43 mg: 1.43 mg: 10.2 mg: 800 μL: 200 μL, heated and stirred at 60 ° C for 2 to 5 hours, 3 hours in this embodiment. Use a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm for standby use; S3-2: Prepare a surface passivation agent solution: use trifluoromethylphenylethylamine iodate (CF3-PEAI) as a surface passivation agent for the perovskite film, the concentration of the passivation agent solution is 1.5 mg / mL, the solvent used is anhydrous isopropanol, shake to dissolve, and filter with a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm for later use; S3-3: In a nitrogen glove box at 20-25°C, a one-step anti-solvent method is used to prepare a perovskite active layer. In this embodiment, the temperature is 22°C. An appropriate amount of perovskite solution is dripped onto the substrate and spread all over. The spin coating process is a two-step spin coating process. The speed and time conditions of the first step are 1000rpm, 10s, and then accelerated to the second step. The speed and time conditions are 5000rpm, 40s. At the 22nd to 18th second before the program, 200μL of ethyl acetate is continuously poured onto the rotating substrate to promote the crystallization of perovskite film. The obtained perovskite film is then annealed. The annealing temperature is 100-120°C. In this embodiment, the temperature is 110°C. The annealing time is 15-40min. In this embodiment, the time is 30min.
[0032] S3-4: Modify and passivate the perovskite surface: set the rotation speed to 5000 rpm for 50 seconds; during the high-speed rotation of the perovskite film, add 10 to 20 μL of an isopropanol solution of trifluoromethylphenylethylamine iodate to the center of the perovskite film, 15 μL in this embodiment; then anneal at 90°C for 3 minutes.
[0033] S4: Preparation of electron transport layer: S4-1: using vacuum thermal evaporation to deposit lithium fluoride (LiF) with a thickness of 0.5-1 nm on the surface of the perovskite film as a passivation layer, which is 1 nm in this embodiment; S4-2: Continue to deposit and prepare carbon 60 (C60) with a thickness of 20-40 nm as an electron transport layer by vacuum thermal evaporation method, and in this embodiment, it is 20 nm; S4-3: Continue to evaporate 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP, bathocuproin) with a thickness of 6 nm using a vacuum thermal evaporation method.
[0034] S5: Preparation of metal electrodes: S5-1: Vacuum evaporation of silver electrodes on the electron transport layer, with a vacuum degree of less than 5×10 -4 The evaporation rate is 1.5 angstroms per second, and the electrode thickness is 90nm~120nm, which is 100nm in this embodiment.
[0035] S5-2: Preparation of anti-reflection layer: A LiF layer with a thickness of 105-110 nm is deposited on the surface of the electrode by vacuum thermal evaporation method as an anti-reflection layer, and in this embodiment, the thickness is 110 nm, to increase the photocurrent.
[0036] Example 2: The implementation of this example is basically the same as that of Example 1, except that the material ratio of the perovskite precursor solution prepared in step S3 of this example is different. The specific preparation process is as follows: S3: Preparation of perovskite active layer: Preparation of perovskite precursor solution: MDA in this experimental group 2+ The doping concentration of the cation is 0.75 mol%. Specifically, a perovskite precursor solution containing lead iodide (PbI2), lead bromide (PbBr2), cesium iodide (CsI), methylamine iodide (FAI), methylamine bromide (MABr), and methylenediamine dihydrochloride (MDACl2) with DMF and DMSO as a mixed solvent is prepared, and the feed ratio of each substance is 507 mg: 154.14 mg: 18.2 mg: 192.5 mg: 23.5 mg: 1.25 mg: 800 μL: 200 μL, heated and stirred at 60 ° C for 2 to 5 hours, and 3 hours in this embodiment. Use a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm to filter and set aside.
[0037] The band gap of the perovskite film material in this embodiment is about 1.68 eV, which belongs to a wide band gap perovskite solar cell. The band gap width is adjusted by adjusting the ratio of the perovskite precursor materials to adjust the forbidden band width of the perovskite film material, that is, the band gap value. The external quantum efficiency of the perovskite solar cell prepared in Example 2 of the present invention is tested, and the first-order derivative of the obtained external quantum efficiency curve is taken. The result is as follows: Figure 3 As shown, the band gap of the prepared perovskite is 1.68 eV.
[0038] Example 3: The implementation of this example is basically the same as that of Example 2, except that in this example, when preparing the perovskite precursor solution in step S3, methylenediamine dihydrochloride (MDACl2) is replaced with methylenediamine diiodate (MDAI2), and the concentration of methylenediamine diiodate (MDAI2) in the perovskite precursor solution is 3.15 mg / mL, and other conditions are the same; in this experimental group, MDA 2+ The doping concentration of cations is the same as 0.75mol%; Comparative Example 1 The implementation method of this comparative example is basically the same as that of Example 1, except that methylenediamine dihydrochloride is not added in step S3 of this comparative example, and other conditions remain the same.
[0039] Comparative Example 2 The implementation method of this comparative example is basically the same as that of Example 2, except that methylenediamine dihydrochloride is not added in step S3 of this comparative example, and other conditions remain the same.
[0040] Performance Testing The solar cells prepared in Example 1 and Comparative Example 1 were subjected to current-voltage ( JV ) test, taking the average value of 10 parallel groups in each group, and obtaining JV Curve and the photoelectric conversion efficiency of the battery. JV Curve contrast Figure 2 The photovoltaic parameters are summarized in Table 1. It can be seen that the photoelectric conversion efficiency of the experimental group device is 25.68%, and the conversion efficiency of the control group is 24.50%. It can be seen that the experimental group battery is significantly better than the control group device.
[0041] Table 1 Test results of photovoltaic performance of cells in Example 1 and Comparative Example 1
[0042] The same method was used for the perovskite solar cells of Example 2, Example 3 and Comparative Example 2. JV Curve test, the results are as follows Figure 4 The performance parameters are summarized in Table 2: Table 2 Test results of photovoltaic performance of cells in Example 2, Example 3 and Comparative Example 2
[0043] Combining Table 2 and Figure 4 It can be seen that the methylenediamine cation (MDA 2+ ) doped perovskite solar cells have higher photoelectric conversion efficiency, which is significantly better than that of the undoped methylenediamine cation (MDA) in Comparative Example 2. 2+ ) prepared device.
[0044] 2. Preparation of Copper Indium Gallium Selenide (CIGS)-Perovskite Tandem Solar Cells Example 4: This example provides a method for preparing a copper indium gallium selenide (CIGS)-perovskite tandem solar cell, wherein the tandem cell structure is as follows: Figure 5 As shown, the preparation process includes the following steps: S1: Setting up the battery base: S1-1: Clean a copper indium gallium selenide bottom cell with a size of 2.5 cm×2.5 cm with a nitrogen gas flow, and then treat it with UV-ozone for 15 to 20 minutes, 15 minutes in this embodiment; the copper indium gallium selenide bottom cell includes a stainless steel substrate, a metal Mo layer, a copper indium gallium selenide active layer, a cadmium sulfide layer, an intrinsic zinc oxide layer, and an aluminum zinc oxide (AZO) layer stacked in sequence.
[0045] S1-2: Sputtering ITO layer: Place the prepared CIGS cell into the physical vapor deposition equipment and sputter an ITO intermediate composite layer with a thickness of 15-30 nanometers. The specific parameters are: the chamber base pressure is less than 6×10 -6 Torr; the working pressure is 0.6mTorr; the sputtering power is 50W; the argon flow rate and oxygen flow rate are 15sccm and 0.6sccm respectively. After sputtering, the sample is taken out and annealed at 110℃ in a nitrogen atmosphere for 10-15 minutes.
[0046] S2: Preparation of hole transport layer: S2-1: The specific operation method is the same as step S2 of Example 1.
[0047] S3: Preparation of perovskite active layer: S3-1: Preparation of perovskite precursor solution: prepare a perovskite precursor solution containing lead iodide (PbI2), lead bromide (PbBr2), cesium iodide (CsI), methylammonium iodide (FAI), methylamine bromide (MABr), methylenediamine dihydrochloride (MDACl2) with DMF and DMSO as a mixed solvent, wherein the doping concentration of methylenediamine dihydrochloride (MDACl2) is 0.75 mol%, and the feed ratio of each substance is 507 mg: 154.14 mg: 18.2 mg: 192.5 mg: 23.5 mg: 1.25 mg: 800 μL: 200 μL. Heat and stir at 60°C for 2 to 5 hours, 3 hours in this embodiment, and filter through a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm for use.
[0048] S3-2: preparing a surface passivating agent solution: the specific operation method is the same as step S3-2 of Example 1.
[0049] S3-3: In a nitrogen glove box at 20-25°C, a one-step anti-solvent method is used to prepare a perovskite active layer. In this embodiment, the temperature is 22°C. An appropriate amount of perovskite solution is dripped onto the substrate and spread all over. The spin coating process is a two-step spin coating process. The speed and time conditions of the first step are 1000rpm, 10s, and then accelerated to the second step, the speed and time conditions are 5000rpm, 40s. At the 22nd to 18th second before the program, 400μL of ethyl acetate is continuously poured onto the rotating substrate to promote the crystallization of perovskite film. The obtained perovskite film is then annealed, the annealing temperature is 100-120°C, the temperature in this embodiment is 110°C, and the annealing time is 15-40min, the time in this embodiment is 30min.
[0050] S3-4: Modify and passivate the perovskite surface: The specific operation method is the same as step S3-4 of Example 1.
[0051] S4: Preparation of electron transport layer: S4-1: LiF with a thickness of 0.5-1 nm is deposited on the surface of the perovskite film by vacuum thermal evaporation as a passivation layer; S4-2: C60 with a thickness of 15-20 nm is continuously deposited by vacuum thermal evaporation method as an electron transport layer; S4-3: The sample deposited with C60 was transferred to the chamber of the atomic layer deposition (ALD) equipment, and SnO2 with a thickness of about 20 nm was deposited on the surface of the C60 layer by atomic layer deposition. The parameters were as follows: Tetrakis(dimethylamino)tin(IV) (TDMASn) was used as a tin precursor and stored in a stainless steel container at 60°C. Water was used as an oxidant without active heating. The precursor delivery pipeline was heated to 150°C. Deposition was performed at 80°C, and the TDMASn / wait / H2O / wait times were 0.015s / 10s / 0.05s / 10s, respectively, with a corresponding nitrogen flow rate of 20sccm and a cycle number of 140.
[0052] S5: Preparation of electrodes: S5-1: The sample with the prepared SnO2 layer is transferred to a physical vapor deposition device to sputter a transparent conductive layer of indium zinc oxide (IZO) with a thickness of 40-60 nm, 50 nm in this embodiment, and the specific parameters are: the chamber base pressure is less than 6×10 -6 Torr; the working gas pressure is 0.9mTorr; the sputtering power is 45W; the argon flow rate and oxygen flow rate are 15sccm and 0.6sccm respectively.
[0053] S5-2: Evaporation of metal gate electrode: Vacuum thermal evaporation is used to evaporate a metal silver electrode with a thickness of 300~600nm on and around the top transparent surface, which is 400nm in this embodiment, and the evaporation rate is 1.5~3 angstroms per second, which is 2 angstroms per second in this embodiment.
[0054] S5-3: Evaporation of anti-reflection layer: Vacuum thermal evaporation is used to continue evaporation of LiF with a thickness of 110 nm on the top transparent layer, with an evaporation rate of 0.5-1 angstrom per second, and 1 angstrom per second in this embodiment. Thus, a complete two-terminal copper indium gallium selenide-perovskite tandem solar cell is obtained.
[0055] Comparative Example 3 The implementation method of this comparative example is basically the same as that of Example 4, except that methylenediamine dihydrochloride is not added in step S4 of this comparative example, and other conditions remain the same.
[0056] Performance Testing The CIGS / perovskite tandem solar cells prepared in Example 4 and Comparative Example 3 were subjected to current-voltage ( JV ) test, taking the average value of 10 parallel groups in each group, and obtaining JV The curves and the photoelectric conversion efficiency of the battery, and the photovoltaic parameters are summarized in Table 3: Table 3 Photovoltaic performance test results of cells in Example 4 and Comparative Example 3
[0057] As shown in Table 3, MDA 2+ The photoelectric conversion efficiency of cationic CIGS / perovskite tandem solar cells is significantly better than that of undoped devices.
[0058] 3. Preparation of Perovskite-Perovskite Tandem Solar Cells Example 5: This example provides a method for preparing a perovskite-perovskite tandem solar cell, wherein the perovskite film is passivated simultaneously by two passivating materials. Figure 6 As shown, the preparation process includes the following steps: S1: Setting up the battery base: S1-1: Clean the ITO glass substrate by using detergent, deionized water, ethanol, acetone, and ethanol for ultrasonic cleaning for 15 minutes each. After cleaning, use a nitrogen gas flow to blow dry the substrate, and then treat it with ultraviolet ozone for 15 to 30 minutes, which is 20 minutes in this embodiment.
[0059] S2: Preparation of hole transport layer: S2-1: Preparation of NiO x Nanocrystal aqueous solution: NiO x The nanocrystal powder was added to ultrapure water, the concentration in this example was 10 mg / mL. Oscillation and ultrasound were performed for 5 minutes each. The nanocrystal powder was filtered through a 0.45 μm pore size polytetrafluoroethylene filter membrane and then used for later use. S2-2: Prepare an organic solution of conjugated organic small molecules containing phosphate groups. Specifically, [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz for short) is used to prepare an anhydrous ethanol solution of Me-4PACz with a concentration of 0.5~1.0 mg / mL, 1.0 mg / mL in this embodiment, and oscillate and sonicate for 5~15 minutes each, 10 minutes in this embodiment. Use a 0.45μm pore size polytetrafluoroethylene filter membrane to filter and set aside; S2-3: Take the prepared NiO x The aqueous solution of nanocrystals was spin-coated on an ITO glass substrate at 3000 rpm and then annealed at 150 °C for 15 min in clean air and then immediately transferred to a glove box; S2-4: In a nitrogen glove box, a solution of Me-4PACz in anhydrous ethanol was spin-coated on the prepared NiO at a speed of 3000 rpm. x The substrate was then annealed at 110°C in a glove box for 10 minutes.
[0060] S3: Preparation of perovskite active layer: S3-1: Spin coating deposition to prepare a perovskite layer with a band gap of 1.77 eV, the nominal chemical formula is MDA 0.01 Cs 0.20 FA 0.79 Pb(I 0.6 Br 0.4 )3. Ensure MDA 2+ The cation doping concentration is 1mol%; the perovskite active layer is prepared by a one-step anti-solvent method in a nitrogen glove box at 20-25°C, which is 22°C in this embodiment. An appropriate amount of perovskite solution is dripped on the substrate and spread all over; the spin coating process is a two-step spin coating process, the speed and time conditions of the first step are 1000rpm, 10s, and then accelerated to the second step, the speed and time conditions are 5000rpm, 40s. At the 22nd to 18th second before the program, 200μL of ethyl acetate is continuously flushed on the rotating substrate to promote the crystallization of perovskite film; the obtained perovskite film is then annealed, the annealing temperature is 110°C, the annealing time is 15-30min, which is 20imn in this embodiment.
[0061] S3-2: Modification and passivation of the perovskite surface: p-trifluoromethylphenylethylamine iodate (CF3-PEAI) is used as a surface passivator for the perovskite film. The concentration of the passivator solution is 1.5 mg / mL. The solvent used is anhydrous isopropanol. The film is dissolved by shaking and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm for later use. The rotation speed condition is 5000 rpm for 50 seconds. During the high-speed rotation of the perovskite film, 10 to 20 μL of an isopropanol solution of p-trifluoromethylphenylethylamine iodate is added to the center of the perovskite film, 15 μL in this embodiment. Then anneal at 90°C for 3 minutes.
[0062] S4: Preparation of electron transport layer: S4-1: using vacuum thermal evaporation to deposit LiF with a thickness of 0.5-1 nm on the surface of the perovskite film as a passivation layer, which is 1 nm in this embodiment; S4-2: Continue to deposit C60 with a thickness of 15-25 nm as an electron transport layer by vacuum thermal evaporation, and in this embodiment, it is 20 nm; S4-3: The sample deposited with C60 was transferred to the chamber of the atomic layer deposition (ALD) equipment, and SnO2 with a thickness of about 20 nm was deposited on the surface of the C60 layer by atomic layer deposition. The parameters were as follows: Tetrakis(dimethylamino)tin(IV) (TDMASn) was used as a tin precursor and stored in a stainless steel container at 60°C. Water was used as an oxidant without active heating. The precursor delivery pipeline was heated to 150°C. Deposition was performed at 80°C, and the TDMASn / wait / H2O / wait times were 0.015s / 10s / 0.05s / 10s, respectively, with a corresponding nitrogen flow rate of 20sccm and a cycle number of 140.
[0063] S5: Continue to deposit gold with a thickness of 1-2 nm as a tunneling composite layer by using a vacuum thermal evaporation method, and in this embodiment, the thickness is 1 nm.
[0064] S6: Preparation of hole transport layer: S6-1: Spin coating a poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) hole transport layer on the tunneling composite layer at a rotation speed of 4000 rpm for 30 seconds, and then annealing at 120° C. in air for 20 minutes.
[0065] S7: Preparation of perovskite active layer: S7-1: Spin coating a 1.22 eV bandgap perovskite layer (FA 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3), a one-step anti-solvent method is used to prepare the perovskite active layer in a nitrogen glove box at 20~25℃, which is 22℃ in this embodiment. An appropriate amount of perovskite solution is dropped on the substrate and spread all over; the spin coating process is a two-step spin coating process, the speed and time conditions of the first step are 1000rpm, 10s, and then accelerated to the second step, the speed and time conditions are 5000rpm, 40s. At the 22nd to 18th second before the program, 200μL of ethyl acetate is continuously flushed on the rotating substrate to promote the crystallization of perovskite film; then the obtained perovskite film is annealed, the annealing temperature is 110℃, the annealing time is 15~30min, which is 20min in this embodiment.
[0066] S7-2: Modification and passivation of the perovskite surface: p-Trifluoromethylphenylethylamine iodate (CF3-PEAI) was used as a surface passivator for the perovskite film. The concentration of the passivator solution was 1.5 mg / mL. The solvent used was anhydrous isopropanol. The film was dissolved by shaking and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm for later use. The rotation speed was 5000 rpm for 50 s. During the high-speed rotation of the perovskite film, 10 to 20 μL of an isopropanol solution of p-trifluoromethylphenylethylamine iodate was added to the center of the perovskite film, 15 μL in this embodiment. The film was then annealed at 90°C for 3 min.
[0067] S8: Preparation of electron transport layer: S8-1: Vacuum thermal evaporation is used to deposit a layer of C60 with a thickness of 20-30 nm as an electron transport layer, and in this embodiment, it is 20 nm.
[0068] S8-2: Continue to deposit a layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP, bathocuproin) with a thickness of 6 nm by vacuum thermal evaporation.
[0069] S9: Preparation of electrodes: S9-1: Vacuum thermal evaporation is used to deposit a layer of silver with a thickness of 100-150 nm as the back electrode, 120 nm in this embodiment, to complete the preparation of the entire all-perovskite tandem solar cell.
[0070] 4. Preparation of Silicon-Perovskite Tandem Solar Cells Example 6: This example provides a method for preparing a silicon-perovskite tandem solar cell, wherein the perovskite film is passivated simultaneously by two passivating agent materials. Figure 7 As shown, the preparation process includes the following steps: S1: Setting up the battery base: S1-1: Use n-type single crystal silicon with a thickness of 180 μm or 200 μm as a substrate, texture it to obtain a small textured n-type single crystal silicon substrate, and clean it with hydrofluoric acid and RCA standard.
[0071] S1-2: A plasma enhanced chemical vapor deposition system (PECVD) is used to sequentially deposit a hydrogenated intrinsic amorphous silicon layer (a-Si:H(i)), a phosphorus-doped hydrogenated amorphous silicon layer (a-Si:H(n)), a phosphorus-doped hydrogenated microcrystalline silicon layer (nc-Si:H(n)), and a layer of boron-doped hydrogenated microcrystalline silicon (nc-Si:H(p)) on the front side.
[0072] S1-3: A plasma enhanced chemical vapor deposition system (PECVD) is used to sequentially deposit a hydrogenated intrinsic amorphous silicon layer (a-Si:H(i)) and a boron-doped hydrogenated microcrystalline silicon layer (nc-Si:H(p)) on the back side.
[0073] S1-4: Use PVD equipment to sputter and deposit a transparent conductive layer, such as ITO, on the front and back surfaces respectively.
[0074] S2: Preparation of hole transport layer: S2-1: Deposit a 20~40nm NiO layer on the front ITO by magnetron sputtering x , which is 20 nm in this embodiment.
[0075] S2-2: Spin coating on NiO x Me-4PACz was deposited on the layer.
[0076] S3: Preparation of perovskite active layer: S3-1: Prepare methylenediamine cation (MDA) with a thickness of about 800~1200nm and a band gap of 1.68eV by spin coating, blade coating or slit coating. 2+ )-doped wide bandgap perovskite layer, which is 1000 nm in this embodiment.
[0077] S3-2: Use of trifluoromethylphenethylamine iodide ( p -CF3PEAI) passivation solution was treated on the perovskite surface by spin coating.
[0078] S4: Preparation of electron transport layer: S4-1: Vapor deposit a layer of C60 with a thickness of 15-20 nm as an electron transport layer, and in this embodiment, it is 20 nm.
[0079] S4-2: Use an atomic layer deposition device to deposit a SnO2 layer with a thickness of about 20 nm.
[0080] S4-3: using magnetron sputtering equipment to deposit a 50-80 nm thick IZO transparent conductive layer on SnO2, which is 50 nm in this embodiment.
[0081] S5: Preparation of electrodes: S5-1: Prepare a silver metal grid line electrode by evaporation method, with a thickness of 200-1000 nm, and 800 nm in this embodiment.
[0082] S5-2: Continue to deposit LiF with a thickness of 110 nm on the top transparent layer as an anti-reflection layer by using an evaporation method.
[0083] S5-3: Deposit a layer of silver electrode on the back side by evaporation method to complete the preparation of silicon-perovskite stacked device.
[0084] In summary, the present invention provides a method for effectively improving the stability of halide perovskites, including improving thermal stability, inhibiting ion migration, and solving the problem of halogen segregation in wide-bandgap perovskites, that is, doping a certain amount of methylenediamine cation (MDA) at the A position of the perovskite lattice. 2+ ).
[0085] MDA 2+ The appropriate ion size means that it is a divalent organic cation that can enter the A site of the perovskite lattice. Being able to occupy the A site means that MDA 2+ The cation has better stability and bulk compatibility than other interstitially doped multivalent cations, and has a wider doping concentration window while maintaining beneficial effects; its higher charge number, compared with the conventionally used monovalent A-site cations, can form stronger electrostatic interactions with the easily migrating iodine and bromine anions in perovskite, thereby significantly increasing the migration activation energy of iodine and bromide ions, inhibiting perovskite phase separation, and improving the stability of films and devices.
[0086] In addition, MDA 2+ Cations have strong hydrogen bonding ability, and an MDA 2+ Theoretically, it can form hydrogen bonds with six halogen anions, which is not available for other cations. 2+ The larger ion size of the cation also has a certain steric effect on ion migration. The above three important factors are MDA 2+ The intrinsic reasons why cations can significantly improve the stability of perovskites and devices.
[0087] In summary, high-valent ion doping at the A site of the perovskite lattice inhibits ion migration in the perovskite and suppresses wide-bandgap perovskite phase separation, thereby improving the stability of perovskite materials and devices.
[0088] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the embodiments of the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for improving the stability of metal halide perovskite, characterized in that: A cationic species with a charge number ≥ 2 is doped at the A site of the metal halide perovskite lattice.
2. A method for improving the stability of metal halide perovskite according to claim 1, characterized in that: The cationic species with a charge number ≥ 2 doped in the lattice A site is a salt containing a methylenediamine cation.
3. The method for improving the stability of metal halide perovskite according to claim 1, characterized in that: The metal halide perovskite is an ABX3 type halide perovskite, and the A-site component is CH3NH3 + ,CH(NH2)2 + , one or more combinations of cesium ions; the B position component is one or two combinations of lead ions and tin ions; the X position is one or more combinations of iodine ions, bromide ions, and chloride ions.
4. The method for improving the stability of metal halide perovskite according to claim 1, characterized in that: The method to achieve doping is a solution based method.
5. The method for improving the stability of metal halide perovskite according to claim 2, characterized in that: The salt containing the methylenediamine cation includes one or more of methylenediamine dihydrochloride, methylenediamine dibromide, methylenediamine diiodide, methylenediamine dithiocyanate, methylenediamine diformate, methylenediamine diacetate, methylenediamine oxalate, methylenediamine dibenzoate, and methylenediamine di-p-toluate.
6. The method for improving the stability of metal halide perovskite according to claim 4, characterized in that: The solvent used in the solution-based method is one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, N-methylpyrrolidone, 2-methoxyethanol, isopropanol, and water. The doping concentration is in the range of 0.1-5 mol% relative to the molar concentration of the B-site cation, and the perovskite solution concentration ranges from 1.0 to 2.0 mol / L.
7. The metal halide perovskite material prepared by the method according to any one of claims 1 to 6.
8. The metal halide perovskite film prepared from the metal halide perovskite material according to claim 7.
9. The method for preparing a metal halide perovskite thin film according to claim 8, characterized in that: The preparation method includes one or more of a one-step spin coating method, a two-step spin coating method, a scraper coating method, a slit coating method, a vapor deposition combined with a solution deposition method, an inkjet printing method, and a screen printing method. In the preparation method, the annealing temperature is 90-200°C, the annealing time is 5-60 minutes, and the thickness of the obtained perovskite thin film material is 400-1500nm.
10. Use of the metal halide perovskite film according to claim 8 in optoelectronic devices.
11. The use of the metal halide perovskite thin film in a photoelectric device according to claim 10, characterized in that: The photovoltaic device is a halide perovskite-based solar cell.
12. The use of the metal halide perovskite thin film in a photoelectric device according to claim 11, characterized in that: The solar cell comprises a stacked cell substrate, a hole transport layer, a perovskite active layer, an electron transport layer, and electrodes.
13. The use of the metal halide perovskite film in a photoelectric device according to claim 12, characterized in that: The battery substrate includes a transparent conductive flexible substrate, a transparent conductive glass substrate, a silicon-based solar cell, a CIGS solar cell, a narrow-bandgap perovskite solar cell, and an organic solar cell.
14. The use of the metal halide perovskite thin film in a photoelectric device according to claim 12, characterized in that: The hole transport layer is one or more of a conjugated organic small molecule containing a phosphoric acid group, nickel oxide, CuSCN, CuI, CuS, molybdenum oxide, copper phthalocyanine, copper-nickel composite oxide, a polymer of 3-hexylthiophene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid.
15. The use of the metal halide perovskite film in a photoelectric device according to claim 12, characterized in that: The perovskite active layer is a metal halide perovskite film doped with methylenediamine cations.
16. The use of the metal halide perovskite film in a photoelectric device according to claim 12, characterized in that: The electron transport layer includes one or more of C60, PCBM, SnO2, TiO2, ZnO, SrTiO3, and BaSnO3.
17. The use of the metal halide perovskite film in a photoelectric device according to claim 12, characterized in that: The electrode comprises one or more of gold, silver, copper, carbon, fluorine-doped tin oxide, tin-doped indium oxide, aluminum-doped zinc oxide, indium zinc oxide, indium gallium zinc oxide, cerium oxide-doped indium oxide, and gallium and aluminum co-doped zinc oxide.
Citation Information
Patent Citations
Double-amino organic compound passivation material and application thereof
CN111892504A
Preparation method of perovskite device
CN115942846A
Perovskite thin film, perovskite solar cell and preparation method thereof
CN118019359A
Multiple cation-doped perovskite compound and perovskite solar cell including the same
US20240324448A1
Perovskite compound containing divalent organic cation and device containing the same
WO2021006554A2
Cited By
Method for improving stability of metal halide perovskite and product and application thereof
CN120769679A